IMPLIKASI PUTUSAN MAHKAMAH KONSTITUSI NOMOR79/PUU-XII/2014 TERHADAP KEWENANGAN DEWAN PERWAKILAN DAERAH DALAM PEMBENTUKAN UNDANG-UNDANG - Febriyani Helena Panjaitan; Mustafa Fakhri (Universitas Sumatera Utara, 2019)
ABSTRACT The authority of the Regional Representative Council to be able to submit a draft law along with academic texts to the President contained is not regulated in Undang-Undang Nomor 23 Tahun 2003 and Undang-Undang Nomor 27 Tahun 2009, the provision was deemed unconstitutional so that later the Court Decision No. 92 / PUU-X / 2012 affirms that the Dewan Perwakilan Daerah can submit a draft law along with academic manuscripts to the President and Dewan Perwakilan Rakyat, where the position of the President and the Dewan Perwakilan Rakyat in accepting the bill originating from the DPD is the same, namely receiving Dewan Perwakilan Daerah letters and not copying. Provisions of Article 165 and 166 Law No. 27 of 2009 stipulates that the submission of the Draft Law to be discussed by the President and DPD is related to the Bill as the Dewan Perwakilan Daerah's authority in Article 22D paragraph (1) of the 1945 Constitution of the Republic of Indonesia. While the bill originating from the DPR is related to regional autonomy, central and regional relations, formation and the division and merger of regions, management of natural resources and other economic resources, as well as financial balance between the center and regions, are not regulated to be submitted to the DPD. So that the material contained in Article 165 and 166 Undang-Undang Nomor 27 Tahun 2009 by the Constitutional Court was considered unconstitutional so that in its decision it was stated that the DPD participated in discussing together with the DPR and the President over the Bill relating to its Authority As Article 22D paragraph (1) of the 1945 Constitution of the Republic of Indonesia. Keyword : Regional Representative Council, Constitutional Court, legislation.